ANALISIS DESKRIPTIF UPAYA PENINGKATAN ORIENTASI WIRAUSAHA LAHAN BASAH DI SENTRA KERAJINAN BANJARBARU - Naparin, Muhammad (Lambung Mangkurat University-Indonesia, 2024)
The wetlands of South Kalimantan, which are rich in flora and fauna, play an important role in improving community welfare. To maximize the utilization and added value of wetland potential for the community in sustainability (environment, socio-culture, and economy), efforts were required to improve the entrepreneurial orientation of Micro, Small and Medium Enterprises (MSMEs) located in and around the wetlands. In this study, entrepreneurial orientation was measured by innovativeness, proactiveness, and risk-taking behavior. The urgency of this study were: (1) creating added value of wetland natural resources; (2) creating resilient MSME entrepreneurs based on wetland environments; 3) encouraging the creation of eco-friendly products to replace plastic, (4) creating synergy between wetland environments and the community. This study was performed by implementing measurable training activities equipped with monitoring and evaluation activities for 8 (eight) weeks. Analysis were carried out using descriptive quantitative methods based on the frequency distribution of pre-test and post-test stages. The results showed all elements of the entrepreneurial orientation increased after eight weeks since the training was carried out where the innovativeness score increased from 2.19 to 3.04, proactiveness increased from 2.65 to 3.28, and risk-taking behavior increased from 2.07 to 2.47. Thus, the training activities of entrepreneurial orientation help craftsmen entrepreneurs to increase thier sustainable competitiveness, as well as customer trust, satisfaction and loyalty. In addition, this wetland plant craftsmen training was also an effort to develop environmentally friendly products made from renewable natural resources that will have great potential to replace plastic-based products.